Impact of Metformin Treatment on Human Placental Energy Production and Oxidative Stress - Tarry-Adkins, Jane L.; Robinson, India G.; Reynolds, Rebecca M.; Aye, Irving L. M. H.; Charnock-Jones, D. Stephen; Jenkins, Benjamin; Koulmann, Albert; Ozanne, Susan E.; Aiken, Catherine E. (Frontiers in Cell and Developmental Biology, 2022)
Metformin is increasingly prescribed in pregnancy, with beneficial maternal effects. However, it is not known how metformin-treatment impacts metabolism and energy production in the developing feto-placental unit. We assessed the human placental response to metformin using both in-vivo and in-vitro treated samples. Trophoblasts were derived from placentas collected from non-laboured Caesarean deliveries at term, then treated in vitro with metformin (0.01mM, 0.1mM or vehicle). Metformin-concentrations were measured using liquid-chromatography mass-spectrometry. Oxygen consumption in cultured-trophoblasts was measured using a Seahorse-XF Mito Stress Test. Markers of oxidative-stress were assayed using qRT-PCR. Metformin-transporter mRNA and protein-levels were determined by quantitative RT-PCR and Western-blotting respectively. Metformin concentrations were also measured in sample trios (maternal plasma/fetal plasma/placental tissue) from pregnancies exposed to metformin on clinical-grounds. Maternal and fetal metformin concentrations in vivo were highly correlated over a range of concentrations (R2=0.76, p<0.001; average fetal:maternal ratio 1.5; range 0.8-2.1). Basal respiration in trophoblasts was reduced by metformin treatment (0.01mM metformin; p<0.05, 0.1mM metformin; p<0.001). Mitochondrial-dependent ATP production and proton leak were reduced after treatment with metformin (p<0.001). Oxidative stress markers were significantly reduced in trophoblasts following treatment with metformin. There is a close linear relationship between placental, fetal, and maternal metformin concentrations. Trophoblasts exposed to clinically-relevant metformin concentrations have reduced mitochondrial-respiration, mitochondrial-dependent ATP-production, and reduced markers of oxidative-stress. Given the crucial role of placental energy-production in supporting fetal growth and well-being during pregnancy, the implications of these findings are concerning for intrauterine fetal growth and longer-term metabolic programming in metformin-exposed pregnancies.